2016
DOI: 10.1371/journal.pone.0166482
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Value of Serum Lactate Dehydrogenase in Renal Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundRecently, many studies have shown that the serum lactate dehydrogenase (LDH) level is related to the prognosis of renal cell carcinoma (RCC). We launched this meta-analysis to assess the prognostic value of serum LDH in patients with RCC.MethodsWe searched PubMed, Embase and Web of Science for information on serum LDH and the outcome of RCC through June 14, 2016. The hazard ratio (HR) and its 95% confidence interval (CI) for overall survival (OS) and progression-free survival (PFS) were extracted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 48 publications
2
31
0
1
Order By: Relevance
“…3 ). This result is concurrent with those of previous studies ( 11 , 14 , 21 , 26 ). Furthermore, Spearman's correlation analysis (data not shown) revealed that the serum LDH level has a negative correlation with the expression of LDHD (P=0.028).…”
Section: Resultssupporting
confidence: 93%
“…3 ). This result is concurrent with those of previous studies ( 11 , 14 , 21 , 26 ). Furthermore, Spearman's correlation analysis (data not shown) revealed that the serum LDH level has a negative correlation with the expression of LDHD (P=0.028).…”
Section: Resultssupporting
confidence: 93%
“…Some studies had demonstrated serum LDH could be an effective biomarker to predict the prognosis of small cell lung cancer, renal cell carcinoma and colorectal cancer. [ 36 38 ] In an animal study, Nakamura and Kitagawa [ 39 ] transplanted the human osteosarcomas to nude mice and found LDH could be a biomarker to predict the prognosis of these mice. Some cohort studies also reported serum LDH was an indicator of prognosis in osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that serum C-reactive protein (CRP), ferritin, lactate dehydrogenase (LDH), interleukin (IL)-18, and IL-17A play important roles in the progression of many infectious, inflammatory, malignant and other diseases. [22][23][24][25][26][27] Previous studies have shown a correlation between the severity of MPP and serum CRP, ferritin, LDH, and IL-18. [28][29][30] Although serum IL-17A in MPP has seldom been reported, IL-17A in bronchoalveolar lavage fluid (BALF) has been shown to play critical roles in the occurrence and development of pulmonary diseases, including acute lung injury 31 and MPP.…”
Section: Introductionmentioning
confidence: 98%